2008
DOI: 10.1071/pc080263
|View full text |Cite
|
Sign up to set email alerts
|

Bushfire and the Malthusian guillotine: survival of small mammals in a refuge in Nadgee Nature Reserve, south-eastern New South Wales

Abstract: Following an intense bushfire in December 1972, small mammals were sampled from November 1973 to June 1976 on a few hectares of unburnt, grassy river flat in the Nadgee Nature Reserve, New South Wales. Hindsight shows the importance of these small unburnt patches as refuges for small mammals. A surprising proportion of wildlife survives a large bushfire, but the post-fire population is in extremis, confronted by famine and exposed to increased predation. All small-mammal species on a forest plot burnt in the ?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…For these species, unburnt areas appear to serve as refuges that assist recolonization into the forest as it recovers after wildfire. Although other studies have found unburnt refuges to assist in recolonization (Lunney et al, 2008;Recher et al, 2009), there was little evidence that this is the case for terrestrial mammals in this study, at least at this stage in the post-fire succession, as species occurred at sites in all categories of fire severity and their occurrence at burnt sites did not depend on the amount of nearby unburnt forest. The rapid regeneration of vegetation in ground and shrub layers provides shelter and cover for terrestrial mammals, allowing them to occupy sites that were blackened and bare of living vegetation immediately after the wildfire.…”
Section: Fire Regime Effects At the Site-levelcontrasting
confidence: 56%
See 1 more Smart Citation
“…For these species, unburnt areas appear to serve as refuges that assist recolonization into the forest as it recovers after wildfire. Although other studies have found unburnt refuges to assist in recolonization (Lunney et al, 2008;Recher et al, 2009), there was little evidence that this is the case for terrestrial mammals in this study, at least at this stage in the post-fire succession, as species occurred at sites in all categories of fire severity and their occurrence at burnt sites did not depend on the amount of nearby unburnt forest. The rapid regeneration of vegetation in ground and shrub layers provides shelter and cover for terrestrial mammals, allowing them to occupy sites that were blackened and bare of living vegetation immediately after the wildfire.…”
Section: Fire Regime Effects At the Site-levelcontrasting
confidence: 56%
“…First, the widespread occurrence of most species across all fire severity classes at 2-3 years post fire may be a consequence of survival of sufficient individuals in situ, even though some sites were severely burnt and isolated from unburnt sites. In situ survival of small mammal species was proposed for wet montane forests after this same wildfire (Banks et al, 2011), facilitated by retreating to micro-refuges during or after the fire, such as wombat burrows, large unburnt moist logs, adjacent moist gullies, or floodplains (Lunney et al, 2008;Banks et al, 2011;Bradstock et al, 2005;Garvey et al, 2010). Second, the limited effects of fire-induced landscape heterogeneity may be associated with rapid regeneration of vegetation in the first three years post-fire, allowing rapid re-occupation of burnt areas.…”
Section: Fire Regime Effects At the Landscape-levelmentioning
confidence: 98%
“…With human population growth comes the need to create more space to build homes and grow food, and thus the necessity to alter areas of pristine koala habitat [ 2 ]. Furthermore, when bushfires occur, they are known to wreak havoc on biodiversity [ 26 ]. If not victim to the fire itself, bushfires often leave animals that are otherwise full of vitality threatened by post-fire famine, and the risk of starvation is high [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, moving from education to research was an obvious next step, when the opportunity arose three years later to work with ecologist Harry Recher at the Australian Museum to study the effect of the 1972 fire on the small mammals in Nadgee Nature Reserve (e.g. Recher et al 2009;Lunney et al 2008Lunney et al , 2012. However, I have never forgotten that communicating the science of what was being done remained vital for the everwidening community of interested groups and, therefore, the continuation and expansion of national parks.…”
Section: Looking Back At the 1962 Conference And Nsw In 1970mentioning
confidence: 99%